The role of cobalt in bimetallic iron-cobalt magnetic carbon xerogels developed for catalytic wet peroxide oxidation - Ribeiro, Rui (2017)
Three magnetic carbon xerogels were developed by inclusion of iron and/or cobalt precursors during the synthesis procedure. The synthesized materials were tested in the catalytic wet peroxide oxidation (CWPO) of aqueous solutions containing 4-nitrophenol (4-NP) − a refractory organic model pollutant, under a water treatment process intensification approach. For that p urpose, the experimental runs were performed with high pollutant load (5 g L −1 ), low catalyst dosage (2.5 g L −1 , corresponding to a fixed pollutant/catalyst mass ratio of 2), atmospheric pressure, 50 °C, pH = 3 and stoichiometric amount of hydrogen peroxide (H 2 O 2 ). The bimetallic magnetic carbon xerogel catalyst (CX/CoFe) was more active than each of the monometallic catalysts (CX/Fe or CX/Co). The better performance was explained in terms of a synergic association of factors: (i) the enhanced accessibility to the active iron species at the surface of CX/CoFe promoted by the simultaneous incorporation of cobalt, (ii) the ability of metallic Co to catalyse H 2 O 2 decomposition via hydroxyl radicals (HO[rad]) formation, and (iii) the efficient reduction of Fe 3+ to Fe 2+ promoted by metallic Co on the surface of CX/CoFe. A 4-NP conversion of 98.5% was determined after 30 min of CWPO reaction. Leaching of the iron species in the bimetallic CX/CoFe was considerably reduced with relation to the monometallic iron catalyst. However, partial catalyst deactivation occurred due to lower stability of oxidized cobalt species. A detailed reaction mechanism is proposed for the surface catalytic reactions occurring over the CX/CoFe catalyst.